Pengaruh PDRB Perkapita, Pendidikan dan Kepadatan Penduduk terhadap Jumlah Kriminalitas pada Kabupaten/Kota di Provinsi Jambi - Yolanda Sari; Mainita Mainita; Rosalinda Rosalinda; Muhammad Amali (Ekonomis: Journal of Economics and Business, 2026)
This study aims to analyze the influence of per capita GRDP, education, and population density on crime rates in Jambi Province from 2017 to 2024. The study used panel secondary data analyzed using quantitative descriptive methods and regression analysis using a random effects model (REM). The results show that simultaneously, per capita GRDP, education, and population density significantly influence crime rates in Jambi Province from 2017 to 2024. However, partially, per capita GRDP has a negative and significant effect on crime rates, inversely proportional to population density, which has a positive and significant effect on crime rates. Meanwhile, education has a negative and insignificant effect on crime rates in Jambi Province.